Textile Waste and the Concept of Ownership in the Context of Circular Economy - Kaitazis, Nicoleta (fi=Turun yliopisto|en=University of Turku|, 2018)
The subject of this thesis is the ownership of textile waste. The study is limited to textile waste deriving from households as it is the largest source of textile waste identified in Finland. Today´s consumers purchase large of amounts of textiles per year and discard textiles nearly at the same pace. Unfortunately, most textile waste ends up incinerated due to the current distribution of waste management responsibilities and ultimately, ownership. The study’s objective is to discuss whether ownership can be construed differently in CE in order to increase material recovery of textile waste. The aim of this thesis is to systematize the ownership of textile waste. The systematization is done using theoretical legal dogmatics as the main methodological tool. Despite being based on a Finnish context, the research material is international. Both national and international material is used throughout this study. However, the topic itself is fairly unresearched on national and international level. Therefore, the used research material was searched individually for waste legislation, property law and circular economy and combined to accomplish the objectives of this thesis. The research identified households as the original waste owners. Ownership does not cease to exist when a product becomes waste. The possession of waste is also an indication of ownership. Ownership has been particular viewed from the perspective of the right of disposition. Household’s ownership is, however, very restricted. Textiles waste is categorized as municipal waste to which large amounts of restrictions have been applied to in order to make a change of ownership happen. Households have the obligation to relinquish their textile waste to the municipalities and they are waive their right to disposition over their textile waste once they place the waste into the municipal mixed waste bins. Circular Economy is a new economic model that aims in increasing value creation of companies by shifting the production from open loop to a closed-loop. Circular Economy requires, however, a change in current ownership allocation and content of ownership. However, even in Circular Economy it is not justified that households gain the ownership of their textile waste. From the formulation of various ownership models, Circular Economy seems to shift towards higher levels of producer responsibility. Household’s right to disposition appear in all models restricted.